Khanduri Maulod di Aceh: Interaksi Islam, Modal Sosial, dan Ketahanan Tradisi Keagamaan Lokal - Zuhra Zuhra; M. Syukri Rizki Hamdalah (Al Mabhats : Jurnal Penelitian Sosial Agama, 2024)
Abstract: This study examines how Khanduri Maulod, the Acehnese commemoration of the birth of the Prophet Muhammad, mediates the interaction between Islamic normativity and local cultural practice, and how that interaction is renegotiated under conditions of modernisation and digital mediatisation. Existing scholarship has largely documented the descriptive and normative dimensions of the tradition, yet it has rarely explained the mechanism through which religious meaning is converted into durable social capital, nor has it modelled the tradition as a stratified system. Adopting a qualitative design with a systematic library-based method, the study assembled a corpus of fifty-nine scholarly and journalistic sources published between 2016 and 2026, screened them against explicit inclusion criteria, and analysed them through thematic coding, constant comparison, and source triangulation. The analysis yields four interrelated findings. First, the normative legitimacy of the tradition rests on a bid’ah hasanah argument that reframes innovation as an instrument of religious propagation rather than a deviation from it. Second, the ritual architecture of meudikee, idang meulapeh, and meuramin functions as a moral economy that redistributes surplus toward orphans and the poor. Third, the tradition operates as a reservoir of bonding and bridging social capital that sustains inter-village solidarity across a three-month ritual calendar. Fourth, its contemporary continuity is produced not by cultural inertia but by the deliberate agency of religious scholars, customary leaders, and a digitally literate younger generation. The study contributes a Before–After reconstruction model and a four-level analytical framework normative, ritual, social, and structural-digital that together explain religious resilience as an outcome of reciprocal internalisation and expression rather than of static preservation. These findings offer a transferable analytical instrument for studying vernacular Islam elsewhere in the Muslim world. Abstrak: Penelitian ini mengkaji cara Khanduri Maulod, tradisi masyarakat Aceh dalam memperingati kelahiran Nabi Muhammad SAW, memediasi interaksi antara normativitas Islam dan praktik budaya lokal, serta cara interaksi tersebut dinegosiasikan ulang di tengah modernisasi dan mediatisasi digital. Kajian terdahulu umumnya berhenti pada deskripsi prosesi dan justifikasi normatif, tetapi belum menjelaskan mekanisme konversi makna keagamaan menjadi modal sosial yang tahan lama, dan belum memodelkan tradisi ini sebagai sistem berjenjang. Penelitian menggunakan pendekatan kualitatif dengan metode kepustakaan sistematis: korpus dihimpun dari lima puluh sembilan sumber ilmiah dan jurnalistik terbitan 2016–2026, disaring melalui kriteria inklusi yang eksplisit, lalu dianalisis dengan pengodean tematik, perbandingan tetap, dan triangulasi sumber. Analisis menghasilkan empat temuan yang saling terkait. Pertama, legitimasi normatif tradisi bertumpu pada argumen bid’ah hasanah yang membingkai ulang inovasi sebagai instrumen syiar, bukan penyimpangan. Kedua, arsitektur ritual meudikee, idang meulapeh, dan meuramin bekerja sebagai ekonomi moral yang meredistribusi surplus kepada anak yatim dan fakir miskin. Ketiga, tradisi ini berfungsi sebagai lumbung modal sosial pengikat sekaligus penjembatan yang menopang solidaritas antargampong sepanjang kalender ritual tiga bulan. Keempat, keberlanjutannya hari ini dihasilkan bukan oleh inersia budaya, melainkan oleh agensi terencana ulama, tokoh adat, dan generasi muda yang melek digital. Penelitian ini menyumbangkan model rekonstruksi Before–After dan kerangka analitis empat level normatif, ritual, sosial, serta struktural-digital yang menjelaskan ketahanan tradisi keagamaan sebagai hasil internalisasi dan ekspresi timbal balik, bukan sebagai pelestarian yang statis. Temuan ini menawarkan instrumen analisis yang dapat dialihkan untuk mengkaji Islam vernakular di wilayah Muslim lainnya.